Towards an economic assessment of veterinary inputs in tropical Africa. Based on the work of Carlos Sere - International Livestock Centre for Africa (International Livestock Centre for Africa, 1979)
Presents some of the attempts undertaken to evaluate veterinary measures and their impact on the most relevant diseases in tropical Africa. Compares the methodologies of economic evaluation use. Includes an extensive classified bibliography based on a review of leading publications on the economics of animal health.